Peptična razjeda in okužba s Helicobacter pylori - Skok, Pavel (Medicinski razgledi, 2010)
Gastric and duodenal peptic ulcers are among the most frequent diseases of mankind. Etiological causes for deep gastric and duodenal mucosal lesions are heterogeneous, and among them Helicobacter pylori infection and the use of nonsteroidal-antiinflammatory drugs are most important. Infection with this bacterium is accepted as the main etiological factor for different disease of the upper digestive tract, including gastric cancer. The majority of countries, along with Slovenia, have accepted national guidelines for the treatment of this infection already a decade ago. The indications for its eradication are absolute and elective. Among absolute indications are gastric and duodenal ulcer disease, MALT lymphoma, atrophic gastritis and gastric cancer, while elective indications include functional dyspepsia, gastroesophageal reflux disease and treatment with nonsteroidal-antiinflammatory drugs. Triple antimicrobal therapies based on proton pump inhibitors and two antibiotics are accepted as the therapy of choice. The results of eradication therapies depend on the local Helicobacter pylori resistance rate to antibiotics and patient compliance. The article presents the causes of peptic ulcer, effects of H. pylori colonization of upper gastrointestinal tract mucosa, indications and the most commonly used drug combinations for its eradication.
Keywords: Peptic Ulcer; Peptični ulkus; Helicobacter pylori; Zdravljenje; želodec; Helicobacter Infections; therapy; vnetja; Helicobacter, infekcije